344 LIPOPOLYSACCHARIDE STIMULATES FETAL MOUSE LUNG VASCULOGENESIS. Issue 1 (1st January 2007) - Miller, J. D.; Abrams, N.; Pozzi, A.; Frank, D.; deCaestecker, M.; Prince, L. S.
Abstract : Purpose of Study: Prenatal exposure to bacterial products increases the risk of bronchopulmonary dysplasia (BPD) in extremely preterm infants. Abnormal lung vasculogenesis may be a component of BPD pathogenesis. To test if bacterial products might alter vascular development, we studied the effects of E. coli lipopolysaccharide (LPS) on experimental mouse models of vasculogenesis. Methods: Fetal lung explants were obtained from E16 (term E20) Tie-2-GFP and SCL-YFP mice. Both of these transgenic reporter strains express fluorescent proteins in fetal lung endothelial cells. GFP- and YFP-expressing cells were visualized by confocal microscopy. In vitro vasculogenesis was assayed by culturing immortalized pulmonary microvascular endothelial cells cultured on Matrigel. We measured endothelial cell migration using both a modified Transwell filter system and an artificial wound healing assay. We obtained quantitative image analysis data using Histometrix software. Results: To test the effect of bacterial products on pulmonary vasculogenesis, we cultured saccular stage fetal lung explants from Tie-2 GFP mice for 72 hours in the presence of LPS. In control explants, GFP-expressing endothelial cells were detected around developing saccular airways. Adding LPS to the culture media increased the number of endothelial cells around the airways by 70% ( n = 6, p = .001). We observed similar results using explants from SCL-YFP mice. These observations suggested that LPS might stimulate vasculogenesis in the fetal lung mesenchyme. To test if LPS could directly act on cultured pulmonary microvascular endothelial cells, we measured vasculogenesis in vitro. When cultured on Matrigel, pulmonary microvascular endothelial cells formed elongated capillary-like tube structures. Addition of LPS to the Matrigel and media increased tube length by 45% compared with controls ( n = 6, p < .001). LPS also stimulated pulmonary microvascular endothelial cell migration through gelatin-coated Transwell filters. When cultured on plastic surfaces, LPS-treated endothelia covered artificial wounds in cell monolayers more efficiently than untreated cells ( n = 8, p = .002). These migration data were consistent with in vitro stimulation of vasculogenesis. Conclusions: LPS increased vasculogenesis in our fetal mouse lung explant model and in our in vitro endothelial cell assays. We have yet to determine if LPS subsequently alters capillary remodeling or vascular maturation during alveolar development. These experiments may clarify the mechanisms of abnormal vascular development in BPD.